The pagan stone - Roberts, Nora (Roberts, Nora. Sign of seven trilogy, 2019)
"Years ago, after their blood brother ritual, Gage, Fox, and Caleb each emerged from the woods with a piece of bloodstone. Now, it will become their weapon in the final fight against the demon they awakened. Winner take all... Shared nightmares, visions of blood and fire, and random violence begin to plague the longtime friends and the women bound to them by fate. None of them can ignore the fact that, this year, the demon has grown stronger--feeding off of the terror it creates. But now, the three pieces of the bloodstone have been fused back together. If only they could figure out how to use it. A gambling man like Gage has no trouble betting on his crew to find a way. And though he and Cybil share the gift of seeing the future, that's all they share. But Gage knows that a woman like Cybil--with her brains and strength and devastating beauty--can only bring him luck. Good or bad has yet to be determined--and could mean the difference between absolute destruction or an end to Hawkins Hollow's nightmare..."--Amazon.